Contemporary world regional geography : (McGraw-Hill Higher Education, 2007)
Contemporary World Regional Geography provides a geographical study of world issues through analysis of nine world regions and the countries in each. It integrates the themes of "global connections" and "local voices" and is structured so that within each chapter the global and local tensions are discussed, as well as economic, political, cultural, social, historical, and environmental issues. Each chapter follows the same framework, allowing students to easily make comparisons from one world region to the next.